Improving Quality of Surgical Care and Outcomes: Factors Impacting Surgical Site Infection after Colorectal Resection. Issue 8 (August 2014) - Shaffer, Virginia Oliva; Baptiste, Caitlin D.; Liu, Yuan; Srinivasan, Jahnavi K.; Galloway, John R.; Sullivan, Patrick S.; Staley, Charles A.; Sweeney, John F.; Sharma, Joe; Gillespie, Theresa W.
Surgical site infections (SSIs) result in patient morbidity and increased costs. The purpose of this study was to determine reasons underlying SSI to enable interventions addressing identified factors. Combining data from the American College of Surgeons National Surgical Quality Improvement Project with medical record extraction, we evaluated 365 patients who underwent colon resection from January 2009 to December 2012 at a single institution. Of the 365 patients, 84 (23%) developed SSI. On univariate analysis, significant risk factors included disseminated cancer, ileostomy, patient temperature less than 36°C for greater than 60 minutes, and higher glucose level. The median number of cases per surgeon was 36, and a case volume below the median was associated with a higher risk of SSI. On multivariate analysis, significant risks associated with SSI included disseminated cancer (odds ratio [OR], 4.31; P < .001); surgery performed by a surgeon with less than 36 cases (OR, 2.19; P = .008); higher glucose level (OR, 1.06; P 5.017); and transfusion of five units or more of blood (OR, 3.26; P 5.029). In this study we found both modifiable and unmodifiable factors associated with increased SSI. Identifying modifiable risk factors enables targeting specific areas to improve the quality of care and patient outcomes.